2020
DOI: 10.21203/rs.2.20629/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cholesterol reducer and thrombolytic therapy in acute ischemic stroke patients

Abstract: Background Specific clinical risk factors may contribute to worsening or improving neurological functions in an acute ischemic stroke (AIS) patient pre-treated with a cholesterol reducer with a subsequent recombinant tissue plasminogen activator (rtPA) treatment. We investigated clinical risk factors associated with good or poor presenting neurological symptoms in ischemic stroke patients with prior cholesterol reducer use, specifically a statin and rtPA therapy. Methods We retrospectively analyzed baseline cl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In addition, the severity, mortality and disability rates of patients with a previous stroke history were significantly higher than that of first-ever stroke patients [60]. Moreover, poor neurologic outcomes has been reported in many patients with a previous of stroke [61][62][63][64]. This finding supports our current result of a higher stroke severity among AIS-HF patients in the ≥75 years category with a previous history of stroke.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the severity, mortality and disability rates of patients with a previous stroke history were significantly higher than that of first-ever stroke patients [60]. Moreover, poor neurologic outcomes has been reported in many patients with a previous of stroke [61][62][63][64]. This finding supports our current result of a higher stroke severity among AIS-HF patients in the ≥75 years category with a previous history of stroke.…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings have been reported for AIS patients with histories of previous TIA, [21][22][23] elevated cholesterol levels, 13,24 and direct admission. 25,26 We also observed that AIS patients without HF who did not receive rtPA were more likely to be Hispanic and present with coronary artery stenosis, previous stroke, and elevated lipid level, creatinine, INR, and heart rate. Our finding that Hispanic AIS patients without HF were more likely not to be treated with rtPA is supported by prior studies showing lower rates of rtPA use among the Hispanic population.…”
Section: Discussionmentioning
confidence: 66%